Efeito da Resolvina E1 (RvE1) - mediador lipídico antiinflamatório e pró-resolução - na polpa dental de ratos infectada após exposição ao meio oral - Dondoni, Lenara (2011)
Different approaches have been advocated for implementation of conservative treatment of the pulp tissue, usually employing inflammation control and the application of compounds with therapeutic potential on the pulp. The Resolvin E1 (RvE1) is a lipid mediator capable of regulating inflammatory routes that do not involve the blockage of enzymatic intermediates. The aim of this study was to evaluate the effect of the topical application of RvE1 on dental pulps exposed to the oral environment. To this end, 42 male Wistar rats (n=6 per group/period) had the pulps of the right mandibular first molars assessed and then left exposed to the oral environment for 24 hours. After this period, topical medication either with 0.1% ethanol (vehicle of RvE1), RvE1 or a corticosteroid was applied onto the pulp tissue, and the teeth were then sealed with silver amalgam. The effects of the tested protocols were assessed by histology after 24 and 72 hours. Untouched teeth were used as reference for relative analysis and grading of the alterations observed in test groups. RvE1 induced significant reduction and containment of pulp inflammation with less extensive damage compared to either 0.1% ethanol or corticosteroid (P<0.05). Within the conditions tested none of the tested drugs promoted identical pulp tissue features compared to the observed in untouched teeth (P<0.01). The results presented herein have uncovered protective roles for RvE1 in pulp inflammation, suggesting that it may be a candidate for a novel therapeutic strategy for preservation of its vitality.